2022
DOI: 10.1128/spectrum.00270-22
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance of Nanopore Targeted Sequencing for Diagnosing Infectious Diseases

Abstract: Nanopore targeted sequencing (NTS) is reported to be advantageous in detection speed and range over culture in prior published reports. Investigation of the clinical performance of NTS is deficient at present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Comparison of the performance of those two methods in detecting pathogens in body fluid samples from immunocompromised cancer patients with suspected infections (A, Comparison of the performance of those two methods in detecting pathogens by types of pathogens; B, Comparison of the performance of those two methods in detecting pathogens by types of samples). Morrison et al, 2020;Fu et al, 2022). Therefore, nanopore sequencing has several advantages in detecting causative pathogens compared with RT-qPCR assays or Sanger sequencing-based assays, and can provide more support for the adequate management of infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of the performance of those two methods in detecting pathogens in body fluid samples from immunocompromised cancer patients with suspected infections (A, Comparison of the performance of those two methods in detecting pathogens by types of pathogens; B, Comparison of the performance of those two methods in detecting pathogens by types of samples). Morrison et al, 2020;Fu et al, 2022). Therefore, nanopore sequencing has several advantages in detecting causative pathogens compared with RT-qPCR assays or Sanger sequencing-based assays, and can provide more support for the adequate management of infections.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, metagenomic analyses such as metagenomic next-generation sequencing (mNGS) and nanopore sequencing have emerged as an efficient approach for pathogen detection for patients with infections, which can also detect pathogens in a comprehensive and unbiased way ( Chiu and Miller, 2019 ; Gu et al., 2019 ). The performance of detecting pathogens under different clinical situations between nanopore sequencing and other methods have also been compared in some clinical studies ( Ashikawa et al., 2018 ; Charalampous et al., 2019 ; Chan et al., 2020 ; Deng et al., 2020 ; Morrison et al., 2020 ; Fu et al., 2022 ). Through comparisons with other methods such as culture, RT-qPCR assays and Sanger sequencing-based diagnostics, those studies have confirmed that nanopore sequencing undoubtedly have several advantages such as significantly shorter turnaround time, accurate detection of causative pathogens, simultaneous detection of multiple types of pathogens and accurate detection of antibiotic resistance genes ( Ashikawa et al., 2018 ; Charalampous et al., 2019 ; Chan et al., 2020 ; Deng et al., 2020 ; Morrison et al., 2020 ; Fu et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The target pathogens for HTS identification included bacteria, fungi, mycoplasma, chlamydia, rickettsia, tuberculosis, and other atypical pathogens. Detection procedures have been described elsewhere [ 12 ], and briefly comprised the following steps: (1) sample processing and nucleic acid extraction; we used the Sansure DNA Extraction Kit (Changsha, China); (2) amplification and nanopore targeted sequencing; NTS was built by targeted amplification of the 16s rRNA gene (for bacteria), IST1/2 gene (for fungi), and rpoB (for Mycobacterium spp.) using universal and specific primers, and sequenced by a real-time nanopore sequencing platform; (3) data analysis: sequencing data were divided into samples according to the sequencing tags, adapters were removed, low-quality sequences were filtered, host sequences were removed based on the BLAST and pathogens’ databases, and sequences were annotated; (4) potential pathogen determination: closely related microorganisms were filtered out, contaminants from NTS laboratory sampling and from human normal flora were filtered out by negative controls [ 13 ], and a reportable list of clinical pathogens referenced in published case reports was used [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The sequencing approach has been accelerated by Nanopore-type technologies that require minimal sequencing infrastructure and the ability to sequence anything, anywhere, and anytime by virtually anyone. Even with these clear advantages, to date there have been only a handful of studies investigating the feasibility of AmpSeq or MetaSeq approaches in biodefense applications [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%